Total organic carbon (TOC) and carbon/nittogen ratio in surface sediments of two dominant mangrove species in Getulio, Buenavista, Guimaras. - Lacson, Dina L. (2018.)
Mangroves are able to sequester and store organic carbon in their plant biomass and more importantly in their sediment for long periods of time. The present study aims to determine the Total Organic Carbon (TOC) and Carbon/Nitrogen (C/N) Ratio in surface sediments of two dominant mangrove species (Avicennia marina and Rhizophora mucronata) present within the mangrove estuary of Getulio, Buenavista, Guimaras. The TOC content was determined by Walkley Black titration method, total nitrogen (TN) using macro-Kjeldahl analysis, C/N ratio calculated as TOC/TN and leaf litter fractionation using isolation techniques to separate carbon compounds into three components. Physico-chemical factors vary considerably between two mangrove site locations. Both Avicennia (MA) and Rhizophora (MR) site revealed an alkaline and saline environment suited for mangroge growth and productivity. The total organic carbon content was varying with depth and between the sites, where the highest total average value (4.84±0.62%) was found in the top layer of MA surface sediments and the lowest value (0.72±0.03%) was found at MR surface sediments mangroves planted 2 years after the oil spill incident in Guimaras on August 11, 2006. The TOC of surface sediments at the top 10 cm contained the largest percentage of organic carbon of all depth intervals from each mangrove site. Meanwhile, the C/N ratio of surface sediments decreased from MA to MN and increased from the upper layer to the lower layer. Recalcitrant carbon mainly consisted of lignocelluloses compounds has an inverse relationship with TOC with respect to MA and MR as indicated by increasing TOC in sediment and decreasing lignin and hemicelluloses content. This was accounted to the nature of the mangrove vegetation since MA is mature while MR is young planted. The hydrocarbon biomass index implies that leaf litter had a higher percentage of water-soluble compounds both in MA and MR while individual species also varied in their litter quality characteristics as indicated by the difference in lignin content of A. marina and R. mucronata. The results suggested that Getulio mangrove ecosystem plays an important role in carbon sequestration and organic carbon storage in sediments, reducing greenhouse gases and mitigating effect of climate change.
Thesis (Undergraduate, Bachelor of Sciences in Chemistry) College og Arts and Sciences, University of the Philippines, Miagao, Iloilo. 2018.
Keywords: Mangroves -- Getulio, Buenavista -- Guimars